2020
DOI: 10.1001/jamanetworkopen.2020.5179
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Discordance Between Surrogate Care Goals and Medical Treatment Provided to Older Adults With Serious Illness

Abstract: IMPORTANCE An important aspect of high-quality care is ensuring that treatments are in alignment with patient or surrogate decision-maker goals. Treatment discordant with patient goals has been shown to increase medical costs and prolong end-of-life difficulties. OBJECTIVES To evaluate discordance between surrogate decision-maker goals of care and medical orders and treatments provided to hospitalized, incapacitated older patients. DESIGN, SETTING, AND PARTICIPANTS This prospective cohort study included 363 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 56 publications
(147 reference statements)
0
18
0
Order By: Relevance
“…For patients, it provided assurance that the relatives now knew, and would help ensuring that the preferences would be honoured. The need for relatives to have actual knowledge about the patient’s preferences instead of having to guess when they are asked to speak on behalf of the patient is supported by research showing discordance between surrogate decision-maker goals for care and medical orders and treatments provided to hospitalised, incapacitated older patients [ 27 ]. The physicians found that during the conversations, relatives may support explicating patient preferences, and shed light on possible conflicts between the patient’s and the relative’s opinions.…”
Section: Discussionmentioning
confidence: 99%
“…For patients, it provided assurance that the relatives now knew, and would help ensuring that the preferences would be honoured. The need for relatives to have actual knowledge about the patient’s preferences instead of having to guess when they are asked to speak on behalf of the patient is supported by research showing discordance between surrogate decision-maker goals for care and medical orders and treatments provided to hospitalised, incapacitated older patients [ 27 ]. The physicians found that during the conversations, relatives may support explicating patient preferences, and shed light on possible conflicts between the patient’s and the relative’s opinions.…”
Section: Discussionmentioning
confidence: 99%
“…( 6 ) Higher quality communication with clinical staff can contribute to reducing disparities between interventions and GOC. ( 15 ) The SeeMe™ Care Conference structure facilitates early communication about GOC, and families reported transparent communication about the state of the resident’s health. The SeeMe™ Program seeks to ensure that nurses are equipped to have discussions with families and to verify these preferences “in the moment”, when an acute health event occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Although Danish family members do not have legal rights to make decisions on behalf of the patient without decision-making capacity, family members are involved as the patient’s advocate in presenting the patient’s values and preferences. However, several studies have shown discrepancies between patients’ and families opinions [ 40 ], and therefore discussions with old, sick and frail patients about values, wishes, and preferences should be conducted in a stable disease period whenever possible.…”
Section: Discussionmentioning
confidence: 99%